2016
DOI: 10.1017/s0022377816000398
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar electrodynamics: an unsolved problem

Abstract: Pulsar electrodynamics is reviewed emphasizing the role of the inductive electric field in an oblique rotator and the incomplete screening of its parallel component by charges, leaving 'gaps' with E = 0. The response of the plasma leads to a self-consistent electric field that complements the inductive electric field with a potential field leading to an electric drift and a polarization current associated with the total field. The electrodynamic models determine the charge density, ρ, and the current density, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 100 publications
0
52
1
Order By: Relevance
“…Akin to sGRBs powered by the release magnetic energy stored in magnetars, FRBs may be powered by the release of electrostatic energy stored in pulsars (Katz, 2017a). Provided there are regions of magnetospheric plasma with distinct energy, separated by a vacuum gap, the discharge of such energy could manifest as "pulsar lighting", analogous to the flow of current in the atmosphere when lightning strikes (Melrose and Yuen, 2016). This intense, rapidly varying, electric field in the gaps would accelerate electrons and positrons in the magnetosphere, producing coherent curvature radiation observable as an FRB.…”
Section: Lightning In Pulsarsmentioning
confidence: 99%
“…Akin to sGRBs powered by the release magnetic energy stored in magnetars, FRBs may be powered by the release of electrostatic energy stored in pulsars (Katz, 2017a). Provided there are regions of magnetospheric plasma with distinct energy, separated by a vacuum gap, the discharge of such energy could manifest as "pulsar lighting", analogous to the flow of current in the atmosphere when lightning strikes (Melrose and Yuen, 2016). This intense, rapidly varying, electric field in the gaps would accelerate electrons and positrons in the magnetosphere, producing coherent curvature radiation observable as an FRB.…”
Section: Lightning In Pulsarsmentioning
confidence: 99%
“…These phenomena are thought to originate in the pulsar's magnetosphere and provide insights into the plasma physics of the pulsar emission. Melrose & Yuen (2016) give a recent theoretical overview of possible pulsar emission mechanisms. In the case of modechanging, simultaneous X-ray and radio observations have recently shown that bright and quiet modes switch simul- 1 Apart from various oscillatory modes of the star.…”
Section: Introductionmentioning
confidence: 99%
“…Melrose & Yuen 2016) that is able to produce detectable emission from radio to γ-ray frequencies (e.g. Abdo et al 2010).…”
Section: Introductionmentioning
confidence: 99%